Studies of Reservoir Hosts for Marburg Virus - Swanepoel, Robert; Smit, Sheilagh B.; Rollin, Pierre E.; Formenty, Pierre; Leman, Patricia A.; Kemp, Alan; Burt, Felicity J.; Grobbelaar, Antoinette A.; Croft, Janice; Bausch, Daniel G.; Zeller, Hervé; Leirs, Herwig; et al. (Emerging infectious diseases, 2007)
To determine reservoir hosts for Marburg virus (MARV), we examined the fauna of a mine in northeastern Democratic Republic of the Congo. The mine was associated with a protracted outbreak of Marburg hemorrhagic fever during 1998-2000. We found MARV nucleic acid in 12 bats, comprising 3.0%-3.6% of 2 species of insectivorous bat and 1 species of fruit bat. We found antibody to the virus in the serum of 9.7% of 1 of the insectivorous species and in 20.5% of the fruit bat species, but attempts to isolate virus were unsuccessful.